Legal Strength of Cultivation Rights Certificates Against Community Claims of Physical Land Possession - Julianti Putri Wajim; Tjempaka Tjempaka (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
The land registration system in Indonesia should be able to create legal certainty and protection for every registered land right, including the Right to Cultivate (HGU). The HGU certificate should be a valid and binding proof of rights so that it is not easily disturbed by claims from other parties. However, in reality, disputes still often occur between HGU certificate holders and the community who base claims on physical control of the land or the Statement of Physical Control (SPPF). This condition creates legal uncertainty regarding the evidentiary power of the certificate and the legal status of physical control in the Indonesian land system. This study aims to analyze the legal certainty of HGU certificates against claims of physical control of land and legal protection for HGU holders under Indonesian land law. This study is a library research with a qualitative approach using normative legal research methods through statutory, conceptual, and case approaches. The results of the study indicate that HGU certificates have strong evidentiary power and obtain legal protection as long as they are issued according to procedures, while physical control of the land only stands as factual evidence without providing complete rights until officially registered.